Improving fresh egg waste levels in a Lima warehouse of a producer and distributor company using lean Six Sigma tools and EOQ method - Salazar Renteria, Alejandro Nicolas (2025)
The management of perishable products poses critical challenges in supply chains due to their short shelf life and the risk of economic losses caused by inadequate storage conditions. In the poultry sector, egg production, renowned for its nutritional value, affordability, and versatility, faces high levels of waste. In Peru, where egg production grew by 142.93% between 2005 and 2023, with an annual growth rate of 5.2%, improving storage practices is essential to ensure economic sustainability.This study examines a case in a Peruvian egg production and distribution company, which reported losses of S/.308,181 in 2022 wastes due to overstock and improper storage conditions. Lean Six Sigma tools were implemented to maximize customer value and reduce waste. An EOQ-based inventory policy optimized supply management, while an acceptance sampling strategy reduced the rejection of non-compliant batches in the company’s five main sales channels. The application of these tools was validated using Arena Simulator.The results showed a 49.97% reduction in damaged trays, achieving an accurate calculation of the reorder point (ROP) and the optimal replenishment quantity. Additionally, rejected trays for failing quality standards decreased by 44.44%. Overall, the implementation of these tools resulted in a 39.4% reduction in economic impact. This study highlights the effectiveness of integrating EOQ and acceptance sampling to optimize the management of perishable products, offering replicable solutions for similar challenges in the supply chain.